2016
DOI: 10.15386/cjmed-554
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid as a biomarker of fibrosis in chronic liver diseases of different etiologies

Abstract: Chronic liver diseases represent a significant public health problem worldwide. The degree of liver fibrosis secondary to these diseases is important, because it is the main predictor of their evolution and prognosis.Hyaluronic acid is studied as a non-invasive marker of liver fibrosis in chronic liver diseases, in an attempt to avoid the complications of liver puncture biopsy, considered the gold standard in the evaluation of fibrosis. We review the advantages and limitations of hyaluronc acid, a biomarker, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 72 publications
5
27
0
Order By: Relevance
“…Hence, noninvasive and easily accessible methods of predicting stages of hepatic fibrosis have been developed in human medicine. Consequently, in human patients with hepatic fibrosis, hyaluronic acid (HA), which is an essential component of the extracellular matrix, is widely used as a direct marker for the assessment of hepatic fibrosis . Similarly, in veterinary medicine, several studies have reported that the blood HA concentration is increased in dogs with hepatic disease .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, noninvasive and easily accessible methods of predicting stages of hepatic fibrosis have been developed in human medicine. Consequently, in human patients with hepatic fibrosis, hyaluronic acid (HA), which is an essential component of the extracellular matrix, is widely used as a direct marker for the assessment of hepatic fibrosis . Similarly, in veterinary medicine, several studies have reported that the blood HA concentration is increased in dogs with hepatic disease .…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising since haptoglobin in wellknown marker of liver fibrosis and is incorporated in Fibrotest formula [37]. Serum concentration of hyaluronic acid seems to be biomarker of fibrosis in chronic liver diseases of different etiologies [38] such as non-alcoholic fatty liver disease [39], alcoholic fatty liver disease [40], and viral hepatitis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Among cirrhotic liver subjects, high levels of HA in ALD suggests that the degree of necroinflammation will be varied in different etiologies and it is high in alcohol induced liver injury. HA is produced from activated HSCs after transdifferentiate into myofibroblasts due to inflammation mediated by complex cytokine network [21]. Elevated levels of HA in cirrhotic liver subjects is due to imbalance between synthesis from fibrogenesis and decrease in fibrolysis during the disease progression, dysfunction of sinusoidal endothelial cells leads to reduction in degradation of HA resulting in elevated levels in circulation [8,22].…”
Section: Discussionmentioning
confidence: 99%